UNDISRUPTABLE a mindset of permanent reinventionfor individuals, organisations and life. - MCCULLEN, AIDAN (JOHN WILEY & SONS, 2020)
Understand the barriers to change and cultivate a reinvention mindset that will make you impervious to disruption In our world of incessant change, we are all threatened by volatility, uncertainty, complexity, and ambiguity--at the individual and organizational levels. Undisruptable will give you a new lens through which to consider change as an opportunity rather than an obstacle. You'll be inspired to consider the big questions of today: What does the future hold? What does the exponential growth of technology mean for the world of work? What does a changing job market mean for future generations? What do waves of disruption mean for business leaders? Society is evolving at breakneck speed. What does this mean for all of us? Read Undisruptable to bridge the chaos and build the resilience you need to move forward. While we cannot see into the future, there are repeatable patterns that we can understand. Undisruptable demystifies the principles of change through a blend of analogies, innovation frameworks and exemplars of change such as Fujifilm and Arnold Schwarzenegger. The first step to becoming undisputable is to realize that evolution is a natural part of life, and nature provides many examples. Undisruptable will help you to: Understand the principles of change Overcome the barriers to change See change as an opportunity and not an obstacle Utilize simple frameworks and examples to guide you on your transformation By the end of this book, you will have the essential tools and techniques to foster a reinvention mindset that will help you and your organization to become Undisruptable. This book is part of a 3-part series. Part 2 looks at the biases and mental obstacles that prevent change. Part 3 examines the best ways to communicate change within an organization. PRAISE FOR UNDISRUPTABLE "Aidan McCullen has lived a fascinating life of major change. In his book, 'Undisruptable'; he brings us a method for making sense of the external world, and an accessible and visual approach to letting go of the past, and welcoming the future with a mindset of permanent reinvention. It is a timely, thoughtful book, well worth reading." - Dee Hock, founder and CEO Emeritus of VISA and author of One from Many: VISA and the Rise of Chaordic Organization "As the poet Paul Valery said, 'the future is not what is used to be'. Organizations across the board must come to grips with permanent reinvention as their needed way of being. Aidan McCullen's gifted storytelling will inspire you and get you on your way to permanent reinvention." - Mark Johnson, co-founder Innosight and author Lead from the Future "This book teaches the mindset--the lens of clarity--that we all must develop in order to be undisruptable in a future of chilling disruption." - Bob Johansen author Full-Spectrum Thinking, Distinguished Fellow, Institute for the Future "The snake may slough off its tail, but there's nothing to be sloughed off with this book. Former professional rugby player Aidan McCullen knows how not to be defeated by victory. He knows how to disrupt himself. He knows what it means to be Undisruptable." - Whitney Johnson, author of Disrupt Yourself "Aidan McCullen shows us how to embrace a mindset of permanent reinvention. By reading this book, you will learn how to shed o.